The Effect of Organizational Commitment on Employee Performance with Workability as an Intervening Variable - Misnan, Misnan; Sutawa, Sutawa; Wijayanti Mala, Istiana; Sugiyanto, Lina (Journal of World Science, 2023)
The purpose of this study is to find out and analyze the effect of organizational commitment on employee performance with workability as an intervening variable in the Population and Civil Registry Office of Ngawi Regency. The analysis method used is path analysis. The population in this study was all employees at the Ngawi Regency Population and Civil Registration Service, which amounted to 74 people. The study also used census studies. The results showed that organizational commitment has a positive and significant effect on employee performance in the Population and Civil Registration Service of Ngawi Regency. Work ability has a positive and significant effect on the performance of employees in the Population and Civil Registration Service of Ngawi Regency. It is not proven that organizational commitment has a significant effect on the performance of employees with work ability as an intevining variable in the Ngawi Regency Population and Civil Registration Service.